Acute Pulmonary Edema Caused by a Giant Atrial Myxoma. (15th May 2013) - Fisicaro, Andrea; Slavich, Massimo; Agricola, Eustachio; Marini, Claudia; Margonato, Alberto
Abstract : Atrial myxoma is the most common primary cardiac tumor. Its clinical presentation spreads from asymptomatic incidental mass to serious life-threatening cardiovascular complications. We report the case of a 44-year-old man with evening fever and worsening dyspnea in the last weeks, admitted to our hospital for acute pulmonary edema. The cardiac auscultation was very suspicious for mitral valve stenosis, but the echocardiography revealed a huge atrial mass with a diastolic prolapse into mitral valve orifice causing an extremely high transmitral gradient pressure. Awareness of this uncommon acute presentation of atrial myxoma is necessary for timely diagnosis and prompt surgical intervention.